Productivity in the Netherlands - Ando, Sakai (IMF Working Papers; Working Paper ;, 2020)
Although GDP growth in the Netherlands has recently been stronger than in peer countries, the main contributor has been the growth in labor. If GDP is divided by labor, productivity growth appears to have been slower than in peers. This chapter discusses both exogenous and endogenous factors behind the disappointing productivity growth in the Netherlands and derives policy implications.